2017
DOI: 10.1038/sigtrans.2016.36
|View full text |Cite
|
Sign up to set email alerts
|

Neurons generated from carcinoma stem cells support cancer progression

Abstract: Recent evidences show that nervous system acts as a crucial part of cancer microenvironment. Infiltration of nerve fibers into cancer microenvironment has an important active role in cancer progression. The stimulations of both cancer growth and metastasis by members of nervous system such as neurons and glial cells have been demonstrated. However, how the nervous system is built in cancer is largely unknown. Here we show that a fraction of cancer stem cells (CSCs) derived from patients with gastric carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 33 publications
2
95
0
Order By: Relevance
“…Considering cancer heterogeneity, it might be that cells at different stages of a cancer type or of different cancer types express different subsets of neural genes. Besides our observation, a recent work also reported neuronal differentiation of gastric cancer stem cells (24). It is likely that among other chromatin modification enzymes with neural specific expression identified in the study, some should also regulate neuronal differentiation in cancer cells.…”
Section: Cancer Cells Can Be Terminally Differentiatedsupporting
confidence: 83%
See 1 more Smart Citation
“…Considering cancer heterogeneity, it might be that cells at different stages of a cancer type or of different cancer types express different subsets of neural genes. Besides our observation, a recent work also reported neuronal differentiation of gastric cancer stem cells (24). It is likely that among other chromatin modification enzymes with neural specific expression identified in the study, some should also regulate neuronal differentiation in cancer cells.…”
Section: Cancer Cells Can Be Terminally Differentiatedsupporting
confidence: 83%
“…Numerous studies have reported the importance of neural development signals during cancer development and progression, including those listed in supplemental Tables S4 -S6. Many cancer types, such as gastric and colon cancer, show neurogenesis and increases in nerve density (24,46,47), and denervation suppresses cancer (47). Benign prostatic basal cells that are enriched for stem cell and neural/neuronal genes are associated with more aggressive potential (48).…”
Section: Cancer Cells Share a Regulatory Network With Embryonic Neuramentioning
confidence: 99%
“…Besides, colorectal and gastric cancer stem cells show neuronal differentiation potential [9]. These studies suggest that neural genes and neural properties might play a cell-autonomous role, rather than a mere crosstalk, in promoting tumorigenesis.…”
Section: Introductionmentioning
confidence: 89%
“…The lentiviral vector expressing red fluorescent protein (RFP) under (EF) human elongation factor‐1 alpha promoter and the corresponding viruses were from Genepharma (Shanghai, China). CoCSC infection was performed as previously described …”
Section: Methodsmentioning
confidence: 99%
“…CoCSC infection was performed as previously described. (24) In vivo xenotransplantation of cancer cells. Studies involving nude mice were approved by the Sichuan University Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%